Research Talk by Prof Roger Harris - Universiti Malaysia Sarawak, Institute of Social Informatics and Technological Innovations (Universiti Malaysia Sarawak (UNIMAS), 2013)
Research Talk by Prof Roger Harris at Sarawak Development Industry (SDI). The talk is mainly about the use of aerial photography in various applications.